The impact of sarcopenia and acute muscle mass loss on long‐term outcomes in critically ill patients with intra‐abdominal sepsis. Issue 5 (30th June 2021) - Cox, Michael C.; Booth, Matthew; Ghita, Gabriela; Wang, Zhongkai; Gardner, Anna; Hawkins, Russell B.; Darden, Dijoia B.; Leeuwenburgh, Christiaan; Moldawer, Lyle L.; Moore, Frederick A.; Efron, Philip A.; Anton, Steven; et al.
Abstract: Background: Sarcopenia is a known risk factor for poor outcomes across many chronic diseases. The impact on outcomes of both pre‐existing sarcopenia and acute muscle wasting (AMW) in acute critical illness caused by sepsis remain unclear. Methods: We conducted a prospective longitudinal cohort study of critically ill patients with intra‐abdominal sepsis utilizing abdominal computed tomography at sepsis onset to determine baseline skeletal muscle index (SMI). Biomarkers of inflammation and catabolism were measured through 28 days while hospitalized. We performed follow‐up evaluations of strength and physical function at 3, 6, and 12 months, with interval CT analyses at 3 and 12 months to evaluate changes in muscle mass. Measured clinical outcomes included development of chronic critical illness (≥14 days in intensive care with persistent organ dysfunction), long‐term functional status, and 1 year mortality. Results: Among 47 sepsis patients enrolled (mean age 53 ± 14 years), half ( n = 23; 49%) were sarcopenic at baseline. Overall, sepsis patients exhibited acute and persistent muscle wasting with an average 8% decrease in SMI from baseline at 3 months ( P = 0.0008). Sarcopenic (SAR) and non‐sarcopenic (NSAR) groups were similar in regards to age and comorbidity burden. SAR patients had greater acute physiologic derangement (APACHE II, 18 vs. 12.5), higher incidence of multiple organ failure (57% vs. 17%), longer hospital (21 vs. 12 days) and intensive care unit length of stays (13 vs. 4 days), and higher inpatient mortality (17% vs. 0%; all P < 0.05). Pre‐existing SAR was a strong independent predictor of early death or developing chronic critical illness (odds ratio 11.87, 95% confidence interval CI 1.88–74.9; P = 0.009, area under the curve 0.880) and was associated with significantly higher risk of 1‐year mortality (34.9% vs. 4.2%, p = 0.007). Lower baseline SMI was also predictive of poor functional status at 12 months (OR 0.89, 95% confidence interval 0.80–0.99; p = 0.039, area under the curve 0.867). Additionally, SAR patients had AMW with persistent muscle mass loss at 3 months that was associated with decreased health‐related quality of life and SF‐36 physical function domains ( P < 0.05). Persistent AMW at 3 months was not predictive of mortality or poor functional status, with return to near‐baseline muscle mass among sepsis survivors by 6 months. Conclusions: Critically ill patients have an acute and persistent loss of muscle mass after intra‐abdominal sepsis, which is associated with decreased health‐related quality of life and physical function at 3 months. However, pre‐existing sarcopenia, rather than persistent acute muscle mass loss at 3 months after sepsis, is independently associated with poor long‐term functional status and increased 1 year mortality.